Multifactor Authentication Requirements for Academic Credential - Ben Calvins Odhiambo; Charles Ochieng’ Oguk (IJRDO -Journal of Computer Science Engineering, 2025)
This paper investigates the current practices for academic credential authentication in Kenyan universities and establishes the functional requirements for a robust multifactor authentication (MFA) system to combat widespread document fraud. Drawing on a mixed-methods research design, primarily descriptive, data was collected through questionnaires, interviews, and observations from selected public and private universities and recruitment agencies. Findings reveal a high prevalence of fake academic credentials (80% of respondent universities experienced cases), highlighting the insufficiency of existing manual and single-factor authentication methods. The study details the observed manual verification processes and, critically, identifies the specific functional requirements necessary for modeling an effective MFA system, providing a scientific answer to a pressing practical issue. This research offers both practical and theoretical significance by enhancing security and integrity in academic credential verification and addressing a clear knowledge gap in this context.